2022
DOI: 10.1016/j.jvacx.2021.100131
|View full text |Cite
|
Sign up to set email alerts
|

Yellow fever vaccination in Brazil: Short-term safety and immunogenicity in juvenile autoimmune rheumatic diseases

Abstract: Highlights We examined 17DD yellow fever vaccine in juvenile autoimmune rheumatic disease patients under low immunosuppression during the recent epidemic in Sao Paulo-Brazil. No serious adverse events were reported and frequencies of mild adverse events were comparable between patients and healthy controls. Immunogenicity parameters against yellow fever vaccine were not hampered in juvenile autoimmune rheumatic disease patients. Peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Clinical trials have identified similar viremia and immunogenic responses between the doses. No serious adverse events were identified in these studies, although the sample size was too small for a safety evaluation (27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 98%
“…Clinical trials have identified similar viremia and immunogenic responses between the doses. No serious adverse events were identified in these studies, although the sample size was too small for a safety evaluation (27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 98%
“…Gelbfieberimpfung) sind kontraindiziert. In 2 kleineren Studien war bei niedriger Methotrexat-Dosis eine Gelbfieberimpfung sicher und führte zu vergleichbarer Seroprotektion 99 , 101 . 12 Orale Impfstoffe können unter Vedolizumab unwirksam sein. …”
Section: Reiseimpfungen Bei Risikogruppenunclassified
“…Firstly, YF17D appears to be well tolerated in infants and children [210,211] with a reactogenicity and overall sideeffects comparable to other parenterally administered vaccines [212]. Apparently, this does even not exclude more vulnerable individuals that are prone to complications due to (some degree of) immune suppression [213,214]. Notably, a similarly promising safety has been observed in children for chimeric ChimeriVax-JE/Imojev [215], being superior to original live-attenuated JEV vaccine JE Sa14-14-2 [216,217].…”
Section: Box 3 -General Vaccine Safetymentioning
confidence: 99%